Peran Filsafat Pendidikan Islam Dalam Peningkatan Kualitas Hidup Siswa: Landasan dan Arahan Pendidikan Berdasarkan Ajaran Islam - Muhammad Dwieky Cahyadien; Ade Nandar; Siti Hanifah Najmal Jannah (Tamadduna: Jurnal Peradaban, 2024)
Islamic education philosophy is a study that examines the essence, goals, and methods of Islamic education. Islamic education philosophy plays an important role in improving the quality of human life. This is because Islamic education philosophy provides a broad and deep understanding of the meaning and purpose of life, and can help people live a more meaningful and beneficial life. Based on this, this study aims to examine the role of Islamic education philosophy in improving the quality of life. This study was conducted using a qualitative approach. Research data were obtained through literature studies. Based on the results of the study, it was found that Islamic education philosophy plays an important role in improving the quality of human life through three dimensions, namely: (1)Provide a foundation and at the same time direct the process of implementation of Education based on Islamic teachings, (2)Criticism and correction of the implementation process, (3)Evaluate the methods of the educational process.